Part-time work in European companies Establishment Survey on Working Time 2004-2005 - Anxo, Dominique; Fagan, Colette; Smith, Mark.; European Foundation for the improvement of living and working conditions (Λουξεμβούργο : Υπηρεσία Επισήμων Εκδόσεων των Ευρωπαϊκών Κοινοτήτων, 2007)
Part-time work is one of the best-known 'atypical' working time arrangements in Europe, shaping working time regimes across countries and mapping work-life balance patterns. In recent years, working time arrangements and work-life balance issues have been the focus of a series of crossnational European surveys. The rate of part-time work varies across countries, as do other aspects of working time arrangements (such as the incidence of long full-time hours or 'unsocial' work schedules), which produce marked country differences in the duration and schedule of working hours (Messenger, 2004).
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Part-time employment -- Europe; Part-time employment -- Law and legislation -- European Union countries; Labor policy -- European Union countries; Electronic books